Response to Treatment with Intravenous Golimumab or Infliximab in Rheumatoid Arthritis Patients: PROMIS Results from the Real-World Observational Phase 4 AWARE Study - Clifton O. Bingham; Shawn Black; Natalie J. Shiff; Stephen Xu; Wayne Langholff; Jeffrey R. Curtis (Rheumatology and Therapy, 2023)
Abstract Introduction To assess changes in the Patient-Reported Outcomes Measurement Information System (PROMIS®) outcomes related to social, mental, and physical well-being after approximately 1 year of intravenous (IV) golimumab or infliximab treatment in patients with rheumatoid arthritis (RA) using real-world evidence from AWARE. Methods AWARE was a prospective, noninterventional, multicenter, observational, U.S.-based phase 4 study of 1270 RA patients who initiated treatment with IV golimumab or infliximab. PROMIS-29 and PROMIS short form (SF) Fatigue 7a and Pain Interference 6b questionnaires were administered at baseline and infusions 2, 5, and 8 (approximately weeks  4, 28, and 52 for IV golimumab and weeks  2, 22, and 46 for infliximab). Mean changes from baseline in all PROMIS-29 domains and respective SFs and response rates for achieving ≥ 3, ≥ 5, or ≥ 10-point improvements were determined. Results Among all patients, baseline mean ± SD PROMIS T-scores were consistent between treatment groups and indicated worse physical function (38.2 ± 6.8 IV golimumab, 38.0 ± 6.9 infliximab), more pain interference (63.0 ± 7.6 IV golimumab, 63.9 ± 7.8 infliximab), and greater fatigue (58.4 ± 9.9 IV golimumab, 59.4 ± 10.0 infliximab) in these patients vs the general U.S. population (T-score = 50). Through the 8th infusion of either treatment, IV golimumab- and infliximab-treated patients achieved meaningful improvements (≥ 3-point improvement in T-scores) in all PROMIS-29 domains and respective SFs, and the proportions of patients with ≥ 3, ≥ 5, or ≥ 10-point improvements in T-scores increased from infusion 2 through infusion 8. Conclusions RA patients treated with IV golimumab or infliximab achieved comparable improvements across social, mental, and physical well-being PROMIS measures. Additionally, PROMIS detected meaningful clinical changes in patient-reported outcomes in both treatment groups. ClinicalTrials.gov registration number NCT02728934.